Receptor for AGEs (RAGE) blockade may exert its renoprotective effects in patients with diabetic nephropathy via induction of the angiotensin II type 2 (AT2) receptor - Sourris, Karly C.; Morley, A. L.; Koitka, A.; Samuel, P.; Coughlan, M. T.; Penfold, S. A.; Thomas, M. C.; Bierhaus, Angelika; Nawroth, Peter Paul; Yamamoto, H.; Allen, T. J.; Walther, T.; et al. (Diabetologia, 2010)
AIMS/HYPOTHESIS: The receptor for AGEs (RAGE) contributes to the development and progression of diabetic nephropathy. In this study, we examined whether the protective effects of RAGE blockade are exerted via modulation of the renal angiotensin II type 2 (AT2) receptor. - METHODS: Control and streptozotocin diabetic mice, wild-type or deficient in the AT2 receptor (At2 knockout [KO]) or RAGE (Rage KO), were studied for 24 weeks. Adenoviral overexpression of full-length Rage in primary rat mesangial cells was also used to determine the effects on AT2 production. - RESULTS: With diabetes, Rage-deficient mice had less albuminuria, and an attenuation of hyperfiltration and glomerulosclerosis as compared with diabetic wild-type and At2 KO mice. Renal gene and protein expression of RAGE was elevated with diabetes. Diabetic Rage KO mice had a greater increase in renal AT2 receptor protein than was seen in diabetic wild-type mice. Diabetes-induced increases in renal cytosolic and mitochondrial superoxide generation were prevented in diabetic Rage KO mice, but enhanced in all At2 KO mice. Adenoviral overexpression of RAGE or AGE treatment decreased cell surface AT2 expression, in association with increasing superoxide generation; both were reversed using antioxidants N-acetylcysteine and apocynin, and soluble RAGE in primary mesangial cells. - CONCLUSIONS/INTERPRETATION: RAGE appears to be a common and key modulator of AT2 receptor expression, a finding that would implicate a newly defined RAGE-AT2 axis in the development and progression of diabetic nephropathy.